2020
DOI: 10.1063/1.5121257
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing signal encoding and transmission in class I and class II neurons via ordinal time-series analysis

Abstract: Neurons encode and transmit information in spike sequences. However, despite the effort devoted to quantify their information content, little progress has been made in this regard. Here we use a nonlinear method of time-series analysis (known as ordinal analysis) to compare the statistics of spike sequences generated by applying an input signal to the neuronal model of Morris-Lecar. In particular we consider two different regimes for the neurons which lead to two classes of excitability: class I, where the fre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A recent work by Estarellas et al (2020) [77], used nonlinear metrics to investigate the encoding and information transmission in time series of sensory neurons. They found that depending on the frequency, specific combinations of neuron/class and coupling-type allow a more effective encoding, or a more effective transmission of the signal.…”
Section: Non-linear Metrics In Neuronal Characterizationmentioning
confidence: 99%
“…A recent work by Estarellas et al (2020) [77], used nonlinear metrics to investigate the encoding and information transmission in time series of sensory neurons. They found that depending on the frequency, specific combinations of neuron/class and coupling-type allow a more effective encoding, or a more effective transmission of the signal.…”
Section: Non-linear Metrics In Neuronal Characterizationmentioning
confidence: 99%
“…Using neuronal models it has been shown that, when a weak (subthreshold) periodic input is perceived by a stochastic neuron, the neuron fires a sequence of spikes with specific properties of ordinal probabilities. The ordinal probabilities depend on the amplitude and on the period of the input signal [28,30] and thus, they may be informative of these features of the signal. It was also found that this encoding mechanism can be enhanced in an ensemble of neurons, when they all perceive the weak signal [31].…”
Section: Entropy Complexity and Ordinal Patterns -mentioning
confidence: 99%
“…We also quantified the degree of complexity of the dynamical behavior using a standard measure of complexity, namely the permutation entropy [32][33][34] . To that end, we extracted all 3-element ordinal patterns from the time series (i.e.…”
Section: Network Dynamicsmentioning
confidence: 99%